Dikotomi Ulama menurut Perspektif Abu Hamid Al-Ghazali - Mutrofin Mutrofin; Izzul Madid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2021)
Islamic Scholars (ulama) have important position in Muslim society, they are not only as references but also as determinants in decisions making process, specially related to the benefit of the ummah, as a result, who can be called ulama is not clear, as a result, ulama are defined according to the interests of certain groups. This article examines the dichotomy of scholars in Al-Ghazali's perspective. This article uses data from literature review sources, especially the works written by Al-Ghazali. This article concludes that Al-Ghazali did a sociological reading of the ulama concept according to the social, political, and life context. At the time of Al-Ghazali, the term ulama had become a certain social status, even this term was juxtaposed with certain types of scholarship. With the various titles of ulama according to their expertise, this condition caused a conflict between them. The goal of each group is to claim the most correct according to their opinion. This article discusses the definition of ulama in Alghazali's perspective along with the standards developed by Alghazali to determine the criteria of the ulama in the context of the Islamic community during he lived that stiil suitable to be applied today.Abstrak: Ulama memiliki posisi yang cukup penting dalam masyarakat, mereka tidak hanya sebagai panutan namunn juga sebagai penentu dalam penggambilan keputusan terkait denggan kemaslahatan umat, akibatnya siapa yang dapat disebut sebagai ulama merupa area yang kadang abu-abu, akibatnya ulama didefinisikan sesuai kepentingan kelompok tertentu. Artikel ini mengkaji tentang dikotomi ulama dalam perspektif Al-Ghazali. Artikel ini mengunakan data dari sumber kajian kepustakaan khususnya karya-karya yangg ditulis oleh Alghazali. Kesimpulan dari artikel ini bahwa Al-Ghazali melakukan pembacaan secara sosiologis atas konsep ulama tersebut sesuai dengan konteks sosial, politik dan kehidupannya. Pada masa Al-Ghazali istilah ulama sudah menjadi status sosial tertentu, bahkan istilah ulama ini disandingkan pada jenis keilmuan tertentu. Dengan berbagai julukan ulama sesuai dengan keahliannya tersebut, memunculkan mereka untuk saling berseteru antara ulama satu dengan lainnya. Tujuannya adalah untuk mengklaim yang paling benar menerut pendapat tertentu. Artikel ini membahas tentang definisi ulama dalam perskpektif Alghazali beserta standar yang dikembang oleh Alghazali untuk mentukan kriteria ulama dalam konteks masyarakat islam saat itu.